2009
DOI: 10.1103/physrevb.79.085304
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser-induced coherent spin dynamics in ferromagneticGa1xMnxAs/GaAsstructures

Abstract: Ultrafast pump-probe magneto-optical spectroscopy is used to study coherent spin dynamics in ferromagnetic semiconductor Ga 1−x Mn x As systems at excitation photon energies E ph both above and below the band gap E g of GaAs. Above E g , the temporal Kerr rotation signal is found to be strongly dependent on pump photon polarization. This polarization dependence, persisting to room temperature, is attributed to spins of electrons photoexcited to the conduction band, and disappears for E ph Ͻ E g . Below the Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…Hand-in-hand with the optimization of the material synthesis, we have developed experimental capabilities based on the MO pump-and-probe method that allows us to simultaneously determine the magnetic anisotropy, Gilbert damping and spin stiffness constants from one consistent set of measured data. The possibility to excite and detect precession of ferromagnetic Mn moments in (Ga,Mn)As by this method has been extensively discussed in previous MO studies (see Methods and Supplementary Notes 6-9 for the detailed description of the method) [30][31][32][33][34][35][36][37][38][39][40][41] . All experiments presented below were performed at 15 K. The anisotropy constants, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hand-in-hand with the optimization of the material synthesis, we have developed experimental capabilities based on the MO pump-and-probe method that allows us to simultaneously determine the magnetic anisotropy, Gilbert damping and spin stiffness constants from one consistent set of measured data. The possibility to excite and detect precession of ferromagnetic Mn moments in (Ga,Mn)As by this method has been extensively discussed in previous MO studies (see Methods and Supplementary Notes 6-9 for the detailed description of the method) [30][31][32][33][34][35][36][37][38][39][40][41] . All experiments presented below were performed at 15 K. The anisotropy constants, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5(a). Here the main feature is the oscillation of the Kerr signal caused by the oscillatory component of magnetization M Z due to the collective precession of the magnetization around its inplane equilibrium orientation at a frequency of ∼4.2 GHz (see inset), as discussed in the literature [22][23][24][25][26][27][28] . The observed precession frequency in the low field limit is well described analytically by the formula,…”
Section: B Long-time Dynamics: Coherent Mn Spin Precessionmentioning
confidence: 99%
“…This includes femtosecond Mn spin canting induced by spin-orbit torques 14,15 via photoexcited non-thermal "transverse" hole spins involving the interplay between spin-orbit and magnetic exchange interaction 16,17 ; femtosecond demagnetization (i.e. decrease of Mn spin amplitude) via dynamical polarization of "longitudinal" holes spins [18][19][20] ; picosecond photoinduced ferromagnetism 21 ; and magnetization precession [22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in earlier studies different conclusions were reported regarding the dominant effect responsible for the transient modulation of magnetic anisotropy that triggers the observed precession of magnetization. 8,14,25 Although the previous wavelength dependent studies of the photoinduced magnetization precession suggested a difference between the precession frequencies for excitations above and below the band gap energy 1,4,26 , there is a lack of systematic spectral investigation of the competing influence of the transient increase of local lattice temperature and hole concentration on precession frequency 15 . Under the description of mean-field theory, pump intensity and ambient temperature dependent experimental studies of magnetization precession in (Ga,Mn)As show that laser heating induced by the optical pumping primarily contributes to changes of magnetic anisotropy 26,27 ,while Hashimoto et al concluded that non-thermal increases in photo-excited hole concentration is responsible for such changes.…”
mentioning
confidence: 99%